Atividade de fosfomonohidrolases presentes em fígado de girino de rã-touro (Lithobates catesbeianus) durante a metamorfose - Santana, Caroline Carla [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The liver is an important organ in animal metabolism, being responsible for the processing and distribution of nutrients through the blood system to other organs and tissues. Since the liver is responsible for various processes of synthesis and concerning the lack of information about the functions of liver acid and alkaline phosphatases, the aim of the study was to analyze the activities of these enzymes involved in phosphorus metabolism of bullfrog's tadpoles (L. catesbeianus) during metamorphosis, aiming to a better understanding about this period of life of the animal and to produce healthy juveniles. Metamorphosis is a crucial stage in amphibian's development, it is characterized by a series of events that enable tadpoles to occupy the terrestrial environment. During metamorphosis and terrestrial adult stage, the acid phosphatase present in the liver acts as an indicator of lysosomal activity, it can be observed by the increase in its activity at the end of the metamorphic climax, suggesting increased cell death due to recycling of nutrients. The liver alkaline phosphatase, a membrane bound enzyme, acts as a phosphomonohydrolase and in the detoxification of compounds, especially phosphate esters generated in animal metabolism. The decrease in alkaline phosphatase activity when an artificial substrate is used demonstrates a reduction in the generation of secondary metabolites because there is no food intake at this stage of life, on the other hand the use of a physiological substrate suggests an important role in protecting the organism.

O fígado é um órgão importante no metabolismo animal, sendo responsável pelo processamento e distribuição dos nutrientes, por meio da corrente sanguínea, para os outros órgãos e tecidos do organismo. Como o fígado é responsável pela realização de vários processos de síntese e tendo em vista a escassez de informação acerca das funções das fosfatases ácida e alcalina hepáticas, o presente trabalho teve por objetivo analisar as atividades dessas enzimas envolvidas no metabolismo de fósforo de girinos de rã-touro (L. catesbeianus) durante a metamorfose, visando gerar maiores informações sobre esse período da vida do animal e obtenção de imagos sadios. A metamorfose é uma etapa crucial no desenvolvimento dos anfíbios, sendo caracterizada por uma série de eventos que possibilitam aos girinos ocuparem o ambiente terrestre. Durante a metamorfose e fase adulta terrestre, a fosfatase ácida presente no fígado atua como um indicador da atividade lisossomal, o que pode ser observado pelo aumento de sua atividade no fim do clímax metamórfico, sugerindo aumento da morte celular devido ao reaproveitamento dos nutrientes. A fosfatase alcalina hepática, uma enzima de membrana, atua como fosfomonohidrolase e na detoxificação, principalmente ésteres de fosfato gerados durante o metabolismo animal. A diminuição da atividade da fosfatase alcalina quando utilizado um substrato artificial, demonstra a queda na geração de compostos secundários, devido a não ingestão de alimentos nessa fase de vida, enquanto que a utilização de um substrato fisiológico sugere um importante papel da mesma na proteção do organismo animal.
Keywords: Rã touro; Fosfatases; Endotoxina; Cinetica de enzimas; Lisossomos; Enzimas; Bullfrog